A Glance on Solar Drying Technology: A Review - Sharikmaslat, Maliq M.; Harge, C. G. (Asian Review of Mechanical Engineering, 2019)
Preservation of fruits, vegetables, and food are essential for keeping them for a long time without further deterioration in the quality of the product. In this review paper, the attention is given on different types of solar drying technologies. There are basically two types of solar drying methods viz, direct type and indirect type. In direct type solar radiations directly fall on the product which is in closed in cabinet and in case of indirect type drying of product can be done by natural or force method. Mixed mode solar drying method is combination of both direct and in direct type. Solar drying has been used to dry plants, seeds, fruits, meat, fish, wood, and other agricultural, forest products. In order to benefit from the free in recent years to develop solar drying mainly for preserving agricultural and forest products.